Poverty in Timor-Leste 2014 - World Bank Group (World Bank, Washington, DC, 2016)
While the Timorese economy has shown signs of faster growth in recent years, and public spending has increased substantially, how the poor have fared through this period has remained largely unknown. The successful conclusion of the third round of the Timor-Leste Survey of Living Standards (TLSLS-3) in April 2015 provides an opportunity to update our understanding of poverty and of many other economic and social conditions. This report provides a detailed assessment of the methodological approaches and headline poverty results from the Timor-Leste Survey of Living Standards 3. The survey is the third in a series of mutually comparable, detailed surveys to assess a wide range of aspects of living standards in Timor-Leste. This survey is the last in the series. It was conducted over a twelve month period from April 2014 to April 2015. This report focuses on providing key results from the TLSLS-3 and a detailed account of the survey methods.